Al Quran dan Perkembangan Ilmu Pengetahuan - Nengsih, Desri (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
The Qur’an is the Kalâmullah which was revealed to the Prophet Muhammad. whose purity is always guarded by Allah. A most perfect holy book that covers all matters relating to life, as well as a source of knowledge and become a guide in human life, because the Qur’an contains verses to read and understand to take lessons. Along with the development of the times with various technological advances, the Qur’an is always able to answer and confront and maintain itself as a holy book that can stand the authenticity, truth and purity. The style of language that no one can match and the knowledge contained therein is clear evidence that it is a divine word. In its journey which is the guideline of human life throughout the ages, which is not only a source of various Islamic disciplines, but also a source of science and technology, the Qur’an is always able to prove that it is a revelation of the truth from God. A number of scientific truths that can only be revealed by humans with 20th century technology were stated in the Qur'an 1400 years ago.